Dose response of alanine detectors irradiated with carbon ion beams - Herrmann, Rochus; Jäkel, Oliver; Palmans, Hugo; Sharpe, Peter; Bassler, Niels (Medical physics, 2011)
Purpose: The dose response of the alanine detector shows a dependence on particle energy and type when irradiated with ion beams. The purpose of this study is to investigate the response behavior of the alanine detector in clinical carbon ion beams and compare the results to model predictions. Methods: Alanine detectors have been irradiated with carbon ions with an energy range of 89-400 MeV/u. The relative effectiveness of alanine has been measured in this regime. Pristine and spread out Bragg peak depth-dose curves have been measured with alanine dosimeters. The track structure based alanine response model developed by Hansen and Olsen has been implemented in the Monte Carlo codeFLUKA and calculations were compared to experimental results. Results: Calculations of the relative effectiveness deviate less than 5% from the measured values for monoenergetic beams. Measured depth-dose curves deviate from predictions in the peak region, most pronounced at the distal edge of the peak. Conclusions: The used model and its implementation show a good overall agreement for quasimonoenergetic measurements. Deviations in depth-dose measurements are mainly attributed to uncertainties of the detector geometry implemented in the Monte Carlo simulations.